Assessment of ergonomic risks in car radio manufacturing using the Suzanne Rodgers and NIOSH criteria: a practical application - Prieto, Newmar Wanderley (2024)
Companies from Industrial Pole of Manaus look for automation to reduce ergonomic risks, even if the degree of autonomy will depend on organizational technical projects, that is, we visualize two different strands to develop ergonomic actions with the objective of improving working conditions related to health and productivity. Many interests about ergonomics are due to legislation, to adapt the work conditions, it is necessary to measure the ergonomic risks through established criteria. The present study aims to verify the contribution of ergonomic risk assessment instruments in practice, even though the process is quite robust, using the NIOSH and Suzanne Rodgers Criteria we visualize several potential to mitigate the risks inside this manufacturing process. The research was conducted through a literature review, and case study, raising the operative mode of all the workstations, mainly considering the comments of the employees involved, since all the methods present had potential for application, but a standardization of the evaluation for data collection become the main factors in determining the risk factors related to musculoskeletal disorders. According to the knowledge acquired and accumulated during the data collection, observed the ergonomic thermometer of the manufacture, where the moderate risk was evident, even if it is a process with automation, but this study will guide to a more effective work in search of the reduction of the ergonomic risk within the organization by the multifunctional team, in the search for the ergonomically correct process.